Consequences of Childhood Exposure to Intimate Partner Violence in Chicago, Illinois, 1994-2000 - Emery, Clifton R. ([Verlag nicht ermittelbar], 2008)
This study used data from the first two waves of the Project on Human Development in Chicago Neighborhoods (PHDCN) to analyze the consequences of childhood exposure to intimate partner violence. The researcher for this study attempted to make four contributions: (1) provide theory driven research in the field of intimate partner violence, (2) do practical research, (3) strike a balance between the resolution of measurement problems and the examination of concrete outcomes, and (4) use high quality data and advanced statistical techniques to adjudicate between conflicting findings in existing literature. The nine data files used in this study were drawn from multiple imputed iterations using the Expectation-Maximization (E.M.) algorithm and data augmentation to address missing data. They included data from two waves of the PHDCN, with 4,955 records for each wave. The data included information for subjects aged 0 to 18 and covered the years 1994 to 2000. The researcher used various scales to measure domestic violence exposer, the impact of exposure on the child's cognitive functioning, the behavioral impact of exposure to domestic violence, anxiety, and the parent-child relationship. Data include the variables that the researcher used to study the effect of domestic violence exposure on not only externalizing, internalizing, and total behavior problems, and academic and cognitive ability, but also truancy, grade repetition, and drug use. This study also contains a selection of variables from several PHDCN studies including those pertaining to intimate partner violence, child abuse, juvenile delinquency, deviance of peers, alcohol use, primary caregiver involvement in the subject's life, and demographics.